MicroRNA‐576‐5p enhances the invasion ability of trophoblast cells in preeclampsia by targeting TFAP2A. Issue 1 (8th November 2019) - Wang, Xiaoning; Peng, Shiyuan; Cui, Kun; Hou, Fangjuan; Ding, Jie; li, Ali; Wang, Mingxia; Geng, Li
Abstract: Background: Preeclampsia (PE) is a common pregnancy‐related syndrome characterized by hypertension and proteinuria, and a major cause of maternal mortality. Therefore, there is an urgent need to identify early biomarkers of PE. The aim of the present study was to identify the functions of miR‐576‐5p in PE. Methods: Effects of miR‐576‐5p and transcription factor AP‐2α ( TFAP2A ) on invasion of human trophoblast HTR8/SVneo cells were investigated. Real‐time quantitative polymerase chain reaction (RT‐qPCR) and western blotting were used to assess the expression of miR‐576‐5p, TFAP2A, E‐cad, and Vimentin in PE tissues and cells. Additionally, immunofluorescence was used to detect the expression of TFAP2A in PE trophoblastic tissue. Subsequently, constructed miR‐576‐5p mimics, miR‐576‐5p inhibitor, and siRNA‐TFAP2A plasmids were transfected into HTR8/SVneo cells for further experiments, including a CCK‐8 assay for cell proliferation, Transwell assay for cell invasion and the luciferase reporter gene system was employed for target verification. Results: A lower expression of miR‐576‐5p and a higher expression of TFAP2A were identified in PE rats. E‐cadherin was highly expressed while Vimentin was downregulated. Further statistical analysis indicated that cell proliferation of HTR8/SVneo cells decreased in the miR‐576‐5p inhibitor group and increased in the miR‐576‐5p mimics and siRNA‐TFAP2A groups. miR‐576‐5p inhibitor suppressed cell invasion, and miR‐576‐5p mimics and siRNA‐TFAP2A improved cell invasion. The analysis of luciferase reporter demonstrated a decreased luciferase activity in miR‐576‐5p mimics group compared with control group, which indicates that TFAP2A may be a target of miR‐576‐5p. Interference of TFAP2A could downregulate E‐cadherin and upregulate Vimentin expression. Conclusion: Overexpression of miR‐576‐5p and knockdown of TFAP2A may elevate cell proliferation and invasion of human trophoblast cells in vitro. Therefore, miR‐576‐5p may be used as a notable biomarker for the diagnosis, prevention, and treatment of PE. miR‐576‐5p targeting TFAP2A deserve further investigation in order to explore their potential role in PE. Abstract : Preeclampsia (PE) is a common pregnancy‐related disease characterized by hypertension and proteinuria, and a major cause of maternal mortality. Therefore, there is an urgent need to identify early biomarkers of PE. The aim of the present study was to identify the functions of miR‐576‐5p in PE.